Zinc ion battery negative electrode current collector and preparation method and application thereof

By setting a metal deposition layer on the conductive substrate of the zinc ion battery, the corrosion, hydrogen evolution and dendrite problems of the negative electrode of the zinc ion battery are solved, the cycle stability and utilization of the battery are improved, and the service life of the battery is extended.

CN119812344APending Publication Date: 2025-04-11BYD CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411682046.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The negative electrode of zinc ion battery has problems such as corrosion, hydrogen evolution, dendrite, etc., which leads to short-circuiting of the battery and rapid attenuation of capacity. The deposition uniformity of zinc on the negative electrode is poor and the utilization rate is low.

Method used

On the conductive substrate is provided a metal deposition layer, including at least one of metal fluoride and metal sulfide, and the metal includes at least one of indium, bismuth, tin, copper, and nickel. This metal deposition layer can alleviate the problem of poor contact between the negative electrode current collector/active material interface of zinc ion battery, inhibit dendrites' growth, and reduce active zinc loss.

Benefits of technology

By providing a metal deposition layer on the conductive substrate, the cycle stability and utilization of zinc ion batteries are improved, the occurrence of dendrites and the loss of active zinc are reduced, thereby extending the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812344A_ABST
    Figure CN119812344A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly discloses a zinc ion battery negative current collector, a preparation method of the zinc ion battery negative current collector, a zinc ion battery negative plate, a zinc ion battery and an electric device. The metal deposition layer is located on at least one side surface of the conductive substrate and comprises a metal deposition material, the metal deposition material comprises at least one of metal fluoride and metal sulfide, and metal in the metal deposition material comprises at least one of indium, bismuth, tin, copper and nickel. Therefore, the zinc ion battery adopting the zinc ion battery negative electrode current collector has relatively high cycling stability and utilization rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of battery technology, and specifically relates to a zinc ion battery negative electrode current collector and a preparation method and application thereof, and more specifically relates to a zinc ion battery negative electrode current collector and a preparation method thereof, an ion battery negative electrode sheet, a zinc ion battery and an electrical device. Background Art

[0002] Neutral aqueous zinc-ion batteries have the outstanding advantages of low cost, high safety, and high energy density, and are expected to replace lithium-ion batteries in large-scale energy storage systems and power battery systems. However, zinc foil negative electrodes have problems such as corrosion, hydrogen evolution, dendrites, and low utilization, which lead to short circuits in the battery and rapid capacity decay. Increasing the uniformity of zinc deposition on the negative electrode and avoiding dendrites as much as possible have always been the goal. Related technologies mainly focus on modifying the electrode material formula and peel strength, but the degree of improvement is limited. Therefore, zinc-ion battery related technologies need to be further improved. Summary of the invention

[0003] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present application proposes a zinc ion battery negative electrode current collector with good cycle stability, high utilization rate or low cost and a preparation method thereof, a zinc ion battery negative electrode sheet, a zinc ion battery and an electric device.

[0004] In the first aspect of the present application, a negative electrode current collector of a zinc ion battery is proposed, comprising: a conductive substrate; a metal deposition layer, located on at least one side surface of the conductive substrate, comprising a metal deposition material, the metal deposition material comprising at least one of metal fluoride and metal sulfide, and the metal in the metal deposition material comprising at least one of indium, bismuth, tin, copper, and nickel. By arranging the metal deposition layer on the conductive substrate, on the one hand, the problem of poor contact between the negative electrode current collector / active material interface of the zinc ion battery after multiple cycles at high utilization can be alleviated, and the problem of dendrites caused by uneven deposition of metal ions at the active material / electrolyte interface can be alleviated; on the other hand, the battery failure phenomenon caused by the loss of active zinc caused by by-products can be alleviated.

[0005] In some embodiments, the thickness of the metal deposition layer is 0.01 μm to 20 μm, thereby allowing for faster and more uniform adsorption of metal ions, further suppressing the loss of active zinc.

[0006] In some embodiments, the metal deposition layer further includes a conductive agent and a binder, thereby enhancing the contact between the metal deposition layer and the conductive substrate and improving the conductivity of the metal deposition layer.

[0007] In some embodiments, the conductive agent includes at least one of conductive carbon black, carbon nanotubes, graphene, Ketjen black, and graphite. Thus, the material source is wide, the cost is low, and it is beneficial to improve the conductivity of the metal deposition layer.

[0008] In some embodiments, the binder includes at least one of polytetrafluoroethylene, cellulose, styrene-butadiene rubber, polyacrylic acid, polyvinylidene fluoride, and sodium alginate. Thus, the material source is wide, the cost is low, and the metal deposition layer can be better bonded to the conductive substrate.

[0009] In some embodiments, based on the total mass of the metal deposition layer, the metal deposition layer includes 70-90% of the metal deposition material, 0-10% of the conductive agent, and 0-10% of the binder in terms of mass percentage, thereby further suppressing the loss of active zinc.

[0010] In some embodiments, the negative electrode current collector of the zinc ion battery further includes a conductive layer, and the conductive layer is located on a side of the metal deposition layer away from the conductive substrate and / or between the metal deposition layer and the conductive substrate, thereby further enhancing the conductivity of the negative electrode current collector of the zinc ion battery.

[0011] In some embodiments, the conductive layer is composed of a conductive agent, and the metal deposition layer is composed of the metal deposition material, thereby further enhancing the conductivity of the negative electrode current collector of the zinc ion battery.

[0012] In some embodiments, the conductive substrate includes at least one of stainless steel foil, copper foil, copper alloy foil, tin foil, aluminum foil, and indium foil. Thus, the material cost is low and the selection is wide.

[0013] In some embodiments, the thickness of the conductive substrate is 5 μm to 50 μm, thereby further improving the cycle stability of the negative electrode current collector of the zinc ion battery.

[0014] The second aspect of the present application provides a method for preparing a negative electrode current collector for a zinc ion battery, comprising:

[0015] mixing a metal deposition material with a solvent to obtain a deposition layer slurry;

[0016] The deposition layer slurry is coated on at least one side surface of a conductive substrate and dried to form a metal deposition layer on the conductive substrate to obtain the negative electrode current collector of the zinc ion battery.

[0017] The above-mentioned preparation method of the present application is simple to operate and easy to realize industrial production, and the prepared zinc ion battery negative electrode collector has good cycle stability and high utilization rate.

[0018] The third aspect of the present application provides a method for preparing a negative electrode current collector for a zinc ion battery, comprising:

[0019] The metal deposition layer is formed on at least one side surface of the conductive substrate by a deposition method to obtain the negative electrode current collector of the zinc ion battery. Therefore, the operation process is simple and industrial production is easy to achieve.

[0020] In some embodiments, the step of forming the conductive layer by a deposition method is performed, and the conductive layer is located on a side of the metal deposition layer away from the conductive substrate or between the metal deposition layer and the conductive substrate. Thus, the operation process is simple and industrial production is easy to achieve.

[0021] In some embodiments, the deposition method includes at least one of electroplating, in-situ growth, vapor deposition, and melt recasting. Thus, the deposition method has a wide selection.

[0022] The fourth aspect of the present application provides a zinc ion battery negative electrode sheet, comprising the zinc ion battery negative electrode current collector provided in the first aspect of the present application or the zinc ion battery negative electrode current collector prepared by the method of the second aspect and the third aspect of the present application. Thus, the zinc ion battery negative electrode sheet has good cycle stability.

[0023] The fifth aspect of the present application provides a zinc ion battery, comprising the zinc ion battery negative electrode sheet provided in the fourth aspect of the present application. Thus, the zinc ion battery has high cycle stability and utilization rate.

[0024] The sixth aspect of the present application provides an electrical device, comprising the zinc ion battery provided in the fifth aspect of the present application. Thus, the electrical device has better comprehensive performance and longer service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic diagram of the structure of the negative electrode current collector of a zinc ion battery according to one embodiment of the present application.

[0026] Figure 2 It is a partial structural schematic diagram of a zinc ion battery negative electrode current collector applied to a battery according to one embodiment of the present application.

[0027] Figure symbols: J1-zinc ion battery negative electrode current collector; 1-conductive substrate; 2-metal deposition layer; 3-active material; 102-zinc ion battery negative electrode current collector / active material interface; 103-active material / electrolyte interface. DETAILED DESCRIPTION

[0028] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.

[0029] This application is based on the inventor's discovery and understanding of the following facts and problems:

[0030] The inventors have found that the reasons for the poor cycle stability and low utilization rate of the negative electrode of zinc-ion batteries are: on the one hand, during charging, due to the uneven distribution of metal ions in the direction perpendicular to the pole piece, the metal is preferentially deposited at the electrolyte / active material interface and the deposition sites are unevenly distributed, resulting in rapid growth of dendrites; during discharge, due to the large current at the current collector / active material interface, the metal is preferentially dissolved at the interface, resulting in poor contact between the active material and the current collector, affecting the cycle stability under high utilization. On the other hand, with the pH fluctuation caused by charging and discharging, a large amount of basic zinc sulfate by-products appear, resulting in serious loss of active zinc. Therefore, the inventors envision developing a low-cost, industrially suitable negative electrode current collector for zinc-ion batteries to solve the problems of poor cycle stability and low utilization of zinc-ion batteries.

[0031] In view of this, the first aspect of the present application proposes a negative electrode current collector for a zinc ion battery, referring to Figure 1 , comprising: a conductive substrate 1; a metal deposition layer 2, located on at least one side surface of the conductive substrate 1, comprising a metal deposition material, the metal deposition material comprising at least one of a metal fluoride and a metal sulfide, the metal in the metal deposition material comprising at least one of indium, bismuth, tin, copper, and nickel.

[0032] When the negative electrode current collector of the zinc ion battery is applied to the battery, the metal deposition layer can react with the active material in situ to generate a fluoride or sulfide interface, inhibit the occurrence of corrosion and side reactions, reduce the generation of basic zinc sulfate, and improve the utilization rate and cycle stability of the metal negative electrode; on the other hand, the metal deposition layer has good zinc affinity and uniformity. During the cycle process, metal ions will be preferentially adsorbed on the surface of the metal deposition layer, uniformly perpendicular to the metal ion concentration of the pole piece, and induce uniform, directional, and reversible deposition of the metal; thus, the cycle stability and utilization rate of the zinc ion battery can be effectively improved.

[0033] It can be understood that the metal deposition material can be indium fluoride or indium sulfide. Among them, indium has a better affinity for zinc. Fluorine or sulfur can inhibit the hydrogen evolution reaction. The hydrogen evolution reaction and zinc deposition are competitive reactions. If the hydrogen evolution reaction is inhibited, zinc deposition will be easier to proceed. Combining the two effects, zinc can be induced to preferentially deposit in the Figure 2 The zinc ion battery is deposited on the negative electrode current collector / active material interface 102, rather than preferentially depositing on the active material / electrolyte interface 103, in order to avoid the growth of zinc toward the diaphragm to form dendrites, which may lead to battery failure.

[0034] In some embodiments, the thickness of the metal deposition layer is 0.01 μm to 20 μm, for example, 0.01 μm, 0.02 μm, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 5 μm, 10 μm, 15 μm or 20 μm, etc. Within the above thickness range, the metal deposition layer can adsorb metal ions more quickly and evenly, thereby further inhibiting the loss of active zinc.

[0035] According to the embodiments of the present application, the metal deposition layer may be composed of a metal deposition material, or may include other components in addition to the metal deposition material. Specifically, according to the requirements of the preparation process, the metal deposition layer may have different compositions and ratios.

[0036] In some embodiments, the metal deposition layer further includes a conductive agent and a binder, thereby enhancing the contact between the metal deposition layer and the conductive substrate and improving the conductivity of the metal deposition layer, while facilitating the preparation by a coating method.

[0037] In some embodiments, the conductive agent includes at least one of conductive carbon black, carbon nanotubes, graphene, Ketjen black, and graphite. Thus, the material source is wide, the cost is low, and it is beneficial to improve the conductivity of the metal deposition layer.

[0038] In some embodiments, the binder includes at least one of polytetrafluoroethylene, cellulose, styrene-butadiene rubber, polyacrylic acid, polyvinylidene fluoride, and sodium alginate. Thus, the material source is wide, the cost is low, and the metal deposition layer can be better bonded to the conductive substrate.

[0039] In some embodiments, based on the total mass of the metal deposition layer, the metal deposition layer includes 70-90% of the metal deposition material, such as 70%, 72%, 75%, 78%, 80%, 82%, 85%, 88% or 90%, etc., the conductive agent 1-10%, such as 1%, 2%, 4%, 6%, 8% or 10%, etc., and the binder 1-10%, such as 1%, 2%, 4%, 6%, 8% or 10%, etc. Thus, zinc can be uniformly deposited preferentially at the interface of the negative electrode current collector / active material, reduce the loss of active zinc, have good bonding strength with the conductive substrate, and also have good conductivity, which is beneficial to improve the comprehensive performance of the zinc ion battery.

[0040] In some embodiments, the negative electrode current collector of the zinc ion battery further includes a conductive layer, and the conductive layer is located on a side of the metal deposition layer away from the conductive substrate or between the metal deposition layer and the conductive substrate, thereby further enhancing the conductivity of the negative electrode current collector of the zinc ion battery.

[0041] In some embodiments, the conductive layer is composed of a conductive agent; and the metal deposition layer is composed of the metal deposition material. This can further enhance the conductivity of the negative electrode current collector of the zinc ion battery. It can be understood that with the above-mentioned component ratio, the conductive layer and the metal deposition layer are more suitable for the deposition method preparation process.

[0042] Furthermore, the conductive agent forming the conductive layer can be the same as the conductive agent mentioned above, for example, at least one of conductive carbon black, carbon nanotubes, graphene, Ketjen black, and graphite. Thus, the material source is wide, the cost is low, and it is beneficial to improve the conductivity of the metal deposition layer.

[0043] In some embodiments, the conductive substrate includes at least one of stainless steel foil, copper foil, copper alloy foil, tin foil, aluminum foil, and indium foil. Thus, the material cost is low and the selection is wide.

[0044] In some embodiments, the thickness of the conductive substrate is 5 μm to 50 μm, for example, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm, etc. This can further improve the cycle stability of the negative electrode current collector of the zinc ion battery.

[0045] The second aspect of the present application provides a method for preparing a negative electrode current collector for a zinc ion battery, comprising:

[0046] S1: Mixing the metal deposition material with the solvent to obtain a deposition layer slurry.

[0047] In this step, the specific method of mixing the metal deposition material with the solvent is not particularly limited and can be selected according to actual conditions. For example, the metal deposition material and the solvent can be directly added to the mixing container for mixing; the solvent can be added to the mixing container first and then the metal deposition material is added to the solvent; or the metal deposition material can be added to the mixing container first and then the solvent is added to the mixing container, etc. After the metal deposition material and the solvent are added to the mixing container, the metal deposition material and the solvent can be mixed more evenly by mechanical stirring, magnetic stirring, ultrasonic treatment, etc.

[0048] It is understandable that the metal deposition layer may also include a binder and a conductive agent. In this case, in this step, the binder, the conductive agent, the metal deposition material and the solvent may be mixed to obtain a deposition layer slurry. The specific mixing method is not particularly limited.

[0049] As an example, the binder, the conductive agent and the solvent can be mixed evenly in a certain proportion to obtain slurry A; the metal deposition material is added to slurry A in a certain proportion to obtain slurry B. Slurry B is mixed evenly at normal pressure and then vacuum mixed, and then normal pressure is restored and mixed for a period of time to make the metal deposition material evenly distributed to obtain a deposition layer slurry. In some embodiments, the temperature of the mixing process is controlled between 0 and 50°C to prevent the temperature from being too high, which may cause decomposition of certain metal deposition materials.

[0050] It can be understood that the metal deposition material, binder, and conductive agent involved in this step can be consistent with those described in the negative electrode current collector of the zinc ion battery in the first aspect, and will not be repeated here. The solvent used to prepare the deposition layer slurry includes but is not limited to N-methylpyrrolidone (NMP).

[0051] S2: coating the deposition layer slurry on at least one side surface of a conductive substrate, and drying the slurry to form a metal deposition layer on the conductive substrate, thereby obtaining the negative electrode current collector of the zinc ion battery.

[0052] In this step, the specific coating and drying operations are not particularly limited and can be performed according to conventional techniques.

[0053] In some embodiments, after a metal deposition layer is formed on a conductive substrate, a negative electrode current collector for a zinc ion battery can be obtained by rolling, and the rolling pressure is between 0 and 30 MPa, for example, 1 MPa, 2 MPa, 5 MPa, 8 MPa, 10 MPa, 15 MPa, 20 MPa, 25 MPa or 30 MPa, etc.

[0054] The third aspect of the present application provides a method for preparing a negative electrode current collector for a zinc ion battery, comprising: forming a metal deposition layer on at least one side surface of a conductive substrate by a deposition method to obtain the negative electrode current collector for the zinc ion battery. Thus, the operation process is simple and industrial production is easy to achieve.

[0055] In some embodiments, the deposition method includes at least one of electroplating, in-situ growth, vapor deposition, and melt recasting. Thus, the deposition method has a wide selection.

[0056] In this article, "in-situ growth" refers to the direct growth of materials on a specific substrate, such as growing a thin film on a metal surface. "Melt recasting" refers to the process of heating a material above its melting point to make it molten, and then re-solidifying the molten material into a desired shape or structure by casting or other methods.

[0057] According to an embodiment of the present application, a metal deposition layer is formed by a deposition method, and a metal deposition material can be directly used as a target material for deposition. In other words, the metal deposition can be composed only of the metal deposition material. At this time, in order to further improve the conductive performance of the metal deposition layer, a conductive layer can be formed on at least one side surface of the metal deposition layer.

[0058] Therefore, in some embodiments, the method further comprises the step of forming a conductive layer by a deposition method, wherein the conductive layer is located on a side of the metal deposition layer away from the conductive substrate and / or between the metal deposition layer and the conductive substrate. Thus, the operation process is simple and industrial production is easy to achieve.

[0059] According to the embodiments of the present application, the conductive agent used to form the conductive layer can be consistent with the conductive agent in the metal deposition layer described above, for example, it can include at least one of conductive carbon black, carbon nanotubes, graphene, Ketjen black, and graphite. Therefore, it has good conductivity and good compatibility with other layer structures.

[0060] The present invention introduces a metal deposition layer on the surface of the conductive substrate, which, on the one hand, helps to reduce the nucleation overpotential and achieve uniform deposition of zinc at the 102 interface; on the other hand, it can generate a fluoride or sulfide interface with the active material in situ to inhibit the loss of active zinc. The operation method is simple and easy to realize industrial production. The obtained negative electrode current collector of zinc ion battery has good cycle stability and high utilization rate.

[0061] The fourth aspect of the present application provides a zinc ion battery negative electrode sheet, comprising the zinc ion battery negative electrode current collector provided in the first aspect of the present application or the zinc ion battery negative electrode current collector prepared by the method of the second aspect of the present application. Thus, the zinc ion battery negative electrode sheet has good cycle stability.

[0062] It can be understood that, in addition to the above-mentioned negative electrode current collector, the negative electrode sheet of the zinc ion battery can also include necessary structures and components of the conventional negative electrode sheet of the zinc ion battery, for example, it can also include a negative electrode active material layer, etc., which will not be elaborated here.

[0063] The fifth aspect of the present application provides a zinc ion battery, comprising the zinc ion battery negative electrode sheet provided in the fourth aspect of the present application. Thus, the zinc ion battery has high cycle stability and utilization rate.

[0064] It can be understood that there is no special restriction on the specific type of the battery, which can be a primary battery or a secondary battery; the shape of the battery can be a cylindrical battery, a square battery or a battery of any other shape, etc., and according to the outer packaging classification, the battery can be a hard shell battery, a soft pack battery, etc.

[0065] It can be understood that, in addition to the zinc ion battery negative electrode sheet mentioned above, the zinc ion battery has the necessary structure and components of a conventional battery, and generally also includes a positive electrode sheet, a separator, an electrolyte and an outer packaging, wherein the positive electrode sheet, the separator and the negative electrode sheet are made into an electrode assembly by winding or lamination process, and the electrode assembly and the electrolyte (including electrolyte, semi-solid electrolyte, solid electrolyte, etc.) are contained in the outer packaging.

[0066] The sixth aspect of the present application provides an electrical device, comprising the zinc ion battery provided in the fifth aspect of the present application. Thus, the electrical device has better comprehensive performance and longer service life.

[0067] In some embodiments, the zinc ion battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0068] The embodiments of the present application are described in detail below.

[0069] Example 1

[0070] The composition and weight percentage of the metal deposition layer are as follows: indium fluoride: 80%; SP: 10%; PVDF: 10%. The preparation method is as follows: PVDF and SP are mixed in proportion, an appropriate amount of NMP is added, and the mixture is uniformly mixed to obtain slurry A; indium fluoride is added to slurry A and mixed uniformly to obtain slurry B, mixed at normal pressure for 2 minutes, then vacuum mixed, further uniformly mixed and bubbles are removed, and normal pressure is restored to mix for a period of time to make the indium fluoride uniformly distributed. Uniformly coated on a stainless steel conductive substrate, dried, and rolled to obtain a negative electrode current collector for a zinc ion battery. The thickness of the metal deposition layer is 5μm, and the thickness of the stainless steel conductive substrate is 10μm.

[0071] Then, zinc powder is coated on the surface of the negative electrode current collector of the zinc ion battery to obtain a negative electrode sheet, and the performance is tested.

[0072] Example 2

[0073] The composition and weight percentage of the metal deposition layer are as follows: indium sulfide: 80%; KS6: 10%; PVDF: 10%. The preparation method is as follows: PVDF and KS6 are mixed in proportion, an appropriate amount of NMP is added, and the mixture is uniformly mixed to obtain slurry A; indium sulfide is added to slurry A in a certain proportion and mixed uniformly to obtain slurry B, mixed at normal pressure for 2 minutes, then vacuum mixed, further uniformly mixed and bubbles are removed, and normal pressure is restored to mix for a period of time to make the indium sulfide uniformly distributed. It is uniformly coated on a copper foil conductive substrate, dried, and rolled to obtain a negative electrode current collector for a zinc ion battery. The thickness of the metal deposition layer is 10 μm, and the thickness of the copper foil conductive substrate is 10 μm.

[0074] Then, zinc powder is coated on the surface of the negative electrode current collector of the zinc ion battery to obtain a negative electrode sheet, and the performance is tested.

[0075] Example 3

[0076] The composition and weight percentage of the metal deposition layer are as follows: indium fluoride: 50%; indium sulfide: 40%; CNT: 5%; PVDF: 5%. The preparation method is as follows: PVDF and CNT are mixed in proportion, an appropriate amount of NMP is added, and the mixture is uniformly mixed to obtain slurry A; indium fluoride and indium sulfide are added to slurry A in a certain proportion and mixed uniformly to obtain slurry B, mixed at normal pressure for 2 minutes, then vacuum mixed, further uniformly mixed and bubbles are removed, and normal pressure is restored to mix for a period of time to make indium fluoride and indium sulfide uniformly distributed. Uniformly coated on the H65 brass foil conductive substrate, dried, and rolled to obtain the negative electrode current collector of the zinc ion battery. The thickness of the metal deposition layer is 10 μm, and the thickness of the H65 brass foil conductive substrate is 10 μm.

[0077] Then, zinc powder was coated on the surface of the negative electrode current collector to obtain a negative electrode sheet, and the performance was tested.

[0078] Example 4

[0079] The composition and weight percentage of the metal deposition layer are as follows: bismuth fluoride: 80%; KS6: 10%; PVDF: 10%. The preparation method is as follows: PVDF and KS6 are mixed in proportion, an appropriate amount of NMP is added, and the mixture is uniformly mixed to obtain slurry A; bismuth fluoride is added to slurry A in a certain proportion and mixed uniformly to obtain slurry B, mixed at normal pressure for 2 minutes, then vacuum mixed, further uniformly mixed and bubbles are removed, and normal pressure is restored to mix for a period of time to make bismuth fluoride uniformly distributed. Uniformly coated on a copper foil conductive substrate, dried, and rolled to obtain a negative electrode current collector for a zinc ion battery. The thickness of the metal deposition layer is 10 μm, and the thickness of the copper foil conductive substrate is 10 μm.

[0080] Then, zinc powder is coated on the surface of the negative electrode current collector of the zinc ion battery to obtain a negative electrode sheet, and the performance is tested.

[0081] Example 5

[0082] The composition and weight percentage of the metal deposition layer are as follows: 80% tin fluoride; 10% SP; 10% PVDF. The preparation method is as follows: PVDF and SP are mixed in proportion, an appropriate amount of NMP is added, and the mixture is uniformly mixed to obtain slurry A; tin fluoride is added to slurry A and mixed uniformly to obtain slurry B, mixed at normal pressure for 2 minutes, then vacuum mixed, further uniformly mixed and bubbles are removed, normal pressure is restored and mixed for a period of time to make the tin fluoride uniformly distributed. Uniformly coated on a stainless steel conductive substrate, dried, and rolled to obtain a negative electrode current collector for a zinc ion battery. The thickness of the metal deposition layer is 5 μm, and the thickness of the stainless steel conductive substrate is 10 μm.

[0083] Then, zinc powder is coated on the surface of the negative electrode current collector of the zinc ion battery to obtain a negative electrode sheet, and the performance is tested.

[0084] Example 6

[0085] The composition and weight percentage of the metal deposition layer are as follows: copper sulfide: 80%; SP: 10%; PVDF: 10%. The preparation method is as follows: PVDF and SP are mixed in proportion, an appropriate amount of NMP is added, and the mixture is uniformly mixed to obtain slurry A; copper sulfide is added to slurry A and mixed uniformly to obtain slurry B, mixed at normal pressure for 2 minutes, then vacuum mixed, further uniformly mixed and bubbles are removed, normal pressure is restored and mixed for a period of time to make the copper sulfide uniformly distributed. Uniformly coated on a stainless steel conductive substrate, dried, and rolled to obtain a negative electrode current collector for a zinc ion battery. The thickness of the metal deposition layer is 5μm, and the thickness of the stainless steel conductive substrate is 10μm.

[0086] Then, zinc powder is coated on the surface of the negative electrode current collector of the zinc ion battery to obtain a negative electrode sheet, and the performance is tested.

[0087] Example 7

[0088] The composition and weight percentage of the metal deposition layer are as follows: nickel fluoride: 80%; SP: 10%; PVDF: 10%. The preparation method is as follows: PVDF and SP are mixed in proportion, an appropriate amount of NMP is added, and the mixture is uniformly mixed to obtain slurry A; nickel fluoride is added to slurry A and mixed uniformly to obtain slurry B, mixed at normal pressure for 2 minutes, then vacuum mixed, further uniformly mixed and bubbles are removed, and normal pressure is restored to mix for a period of time to make the nickel fluoride uniformly distributed. Uniformly coated on a stainless steel conductive substrate, dried, and rolled to obtain a negative electrode current collector for a zinc ion battery. The thickness of the metal deposition layer is 5μm, and the thickness of the stainless steel conductive substrate is 10μm.

[0089] Then, zinc powder is coated on the surface of the negative electrode current collector of the zinc ion battery to obtain a negative electrode sheet, and the performance is tested.

[0090] Example 8

[0091] The composition and weight percentage of the metal deposition layer are as follows: indium fluoride: 80%; SP: 10%; PVDF: 10%. The preparation method is as follows: PVDF and SP are mixed in proportion, an appropriate amount of NMP is added, and the mixture is uniformly mixed to obtain slurry A; indium fluoride is added to slurry A and mixed uniformly to obtain slurry B, mixed at normal pressure for 2 minutes, then vacuum mixed, further uniformly mixed and bubbles are removed, and normal pressure is restored to mix for a period of time to make the indium fluoride uniformly distributed. Uniformly coated on a copper conductive substrate, dried, and rolled to obtain a negative electrode current collector for a zinc ion battery. The thickness of the metal deposition layer is 0.01 μm, and the thickness of the stainless steel conductive substrate is 10 μm.

[0092] Then, zinc powder is coated on the surface of the negative electrode current collector of the zinc ion battery to obtain a negative electrode sheet, and the performance is tested.

[0093] Example 9

[0094] The composition and weight percentage of the metal deposition layer are as follows: indium fluoride: 80%; SP: 10%; PVDF: 10%. The preparation method is as follows: PVDF and SP are mixed in proportion, an appropriate amount of NMP is added, and the mixture is uniformly mixed to obtain slurry A; indium fluoride is added to slurry A and mixed uniformly to obtain slurry B, mixed at normal pressure for 2 minutes, then vacuum mixed, further uniformly mixed and bubbles are removed, and normal pressure is restored to mix for a period of time to make the indium fluoride uniformly distributed. Uniformly coated on a copper conductive substrate, dried, and rolled to obtain a negative electrode current collector for a zinc ion battery. The thickness of the metal deposition layer is 20 μm, and the thickness of the stainless steel conductive substrate is 10 μm.

[0095] Then, zinc powder is coated on the surface of the negative electrode current collector of the zinc ion battery to obtain a negative electrode sheet, and the performance is tested.

[0096] Example 10

[0097] This example prepares an indium sulfide metal deposition layer by electrodeposition and thermal evaporation. An indium chloride electrolyte is used at 50 mA / cm 2 In is deposited on the surface of the copper foil at a current density of about 5 microns. It is then annealed in a sulfur environment to prepare a negative electrode current collector for a zinc ion battery. The thickness of the metal deposition layer is 5 μm, and the thickness of the copper conductive substrate is 10 μm.

[0098] Then, zinc powder is coated on the surface of the negative electrode current collector of the zinc ion battery to obtain a negative electrode sheet, and the performance is tested.

[0099] Embodiment 11

[0100] This example prepares an indium sulfide metal deposition layer by electrodeposition and thermal evaporation. An indium chloride electrolyte is used at 50 mA / cm 2In is deposited on the surface of the carbon-coated copper foil at a current density of about 5 microns. It is then annealed in a sulfur environment to prepare a negative electrode current collector for a zinc ion battery. The thickness of the metal deposition layer is 5 μm, and the thickness of the carbon-coated copper foil conductive substrate is 11 μm.

[0101] Then, zinc powder is coated on the surface of the negative electrode current collector of the zinc ion battery to obtain a negative electrode sheet, and the performance is tested.

[0102] Comparative Example 1

[0103] A stainless steel foil with a thickness of 10 μm was selected as the current collector. Zinc powder was directly coated on the surface of the stainless steel foil to obtain a negative electrode sheet, and the performance was tested.

[0104] The test method is as follows: symmetrical batteries are assembled using the negative electrode sheets of the embodiment and the comparative example, and the negative electrode sheets obtained in the above embodiment are cut into circular electrode sheets with a diameter of 12 mm as the positive and negative electrode sheets of the symmetrical battery. The electrolyte is 2M ZnSO4+0.2MMnSO4 aqueous solution, and a GFA separator is used. The symmetrical battery is assembled in the order of negative electrode shell-negative electrode sheet-diaphragm-electrolyte-positive electrode sheet-gasket-spring-positive electrode shell. The constant current charge and discharge cycle test is carried out, and the test conditions are 6.66mAh; 3.33mA. The specific test steps are: 1. Stand for 10min; 2. Discharge at a constant current of 3.33mA for 2h; 3. Stand for 10min; 4. Charge at a constant current of 3.33mA for 2h, and repeat the first step cycle. The battery is judged to be failed after a sudden drop in the voltage of the charge or discharge curve. When judging whether a short circuit is prone to occur, it is judged as "yes" if the number of cycles is less than 50; and it is judged as "no" if it is greater than 50. The test results are shown in Table 1.

[0105] Table 1 Test results

[0106] Stable cycle number Is short circuit prone to occur? Example 1 128 no Example 2 78 no Example 3 106 no Example 4 117 no Example 5 98 no Example 6 76 no Example 7 85 no Example 8 119 no Example 9 103 no Example 10 124 no Embodiment 11 120 no Comparative Example 1 29 yes

[0107] It can be seen from the data in Table 1 that coating a metal deposition layer on the surface of a conductive substrate can optimize the negative electrode current collector / active material interface and accelerate the deposition of metal ions on the negative electrode current collector side. The metal deposition layer can induce uniform, reversible and dense deposition of metal ions, alleviate their uneven deposition at the active material / electrolyte interface, and alleviate poor contact at the negative electrode current collector / active material interface at high utilization.

[0108] In the present application, unless otherwise clearly specified and limited, a first feature being “above” or “below” a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being “above”, “above”, and “above” a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being “below”, “below”, and “below” a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0109] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0110] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A negative electrode current collector for a zinc ion battery, characterized in that: include: Conductive substrate; The metal deposition layer is located on at least one side surface of the conductive substrate and includes a metal deposition material. The metal deposition material includes at least one of metal fluoride and metal sulfide. The metal in the metal deposition material includes at least one of indium, bismuth, tin, copper and nickel.

2. The zinc ion battery negative electrode current collector according to claim 1, characterized in that The thickness of the metal deposition layer is 0.01 μm to 20 μm.

3. The zinc ion battery negative electrode current collector according to claim 1, characterized in that The metal deposition layer further includes a conductive agent and a binder, and satisfies at least one of the following conditions: The conductive agent includes at least one of conductive carbon black, carbon nanotubes, graphene, Ketjen black, and graphite; The binder includes at least one of polytetrafluoroethylene, cellulose, styrene-butadiene rubber, polyacrylic acid, polyvinylidene fluoride, and sodium alginate; Based on the total mass of the metal deposition layer, in terms of mass percentage, the metal deposition layer includes 70-90% of the metal deposition material; 1-10% of the conductive agent; and 1-10% of the binder.

4. The zinc ion battery negative electrode current collector according to claim 1, characterized in that The invention also includes a conductive layer, which is located on a side of the metal deposition layer away from the conductive substrate and / or between the metal deposition layer and the conductive substrate.

5. The zinc ion battery negative electrode current collector according to claim 4, characterized in that, The conductive layer is composed of a conductive agent; and the metal deposition layer is composed of the metal deposition material.

6. The zinc ion battery negative electrode current collector according to claim 1, characterized in that The conductive substrate includes at least one of stainless steel foil, copper foil, copper alloy foil, tin foil, aluminum foil and indium foil.

7. The zinc ion battery negative electrode current collector according to claim 1, characterized in that The thickness of the conductive substrate is 5 μm to 50 μm.

8. A method for preparing the negative electrode current collector of a zinc ion battery according to any one of claims 1 to 7, characterized in that: include: mixing a metal deposition material with a solvent to obtain a deposition layer slurry; The deposition layer slurry is coated on at least one side surface of a conductive substrate and dried to form a metal deposition layer on the conductive substrate to obtain the negative electrode current collector of the zinc ion battery.

9. A method for preparing a negative electrode current collector for a zinc ion battery according to any one of claims 1 to 7, characterized in that: include: A metal deposition layer is formed on at least one side surface of the conductive substrate by a deposition method to obtain the negative electrode current collector of the zinc ion battery.

10. The method according to claim 9, characterized in that Also includes: The step of forming a conductive layer by a deposition method, wherein the conductive layer is located on a side of the metal deposition layer away from the conductive substrate or between the metal deposition layer and the conductive substrate.

11. The method according to claim 9 or 10, characterized in that: The deposition method includes at least one of electroplating, in-situ growth, vapor deposition, and melt recasting.

12. A zinc ion battery negative electrode sheet, characterized in that: The invention comprises the negative electrode current collector of the zinc ion battery according to any one of claims 1 to 7 or the negative electrode current collector of the zinc ion battery prepared by the method according to any one of claims 8 to 11.

13. A zinc ion battery, characterized in that: Including the zinc ion battery negative electrode sheet as described in claim 12.

14. An electrical device, characterized in that: Including the zinc ion battery as described in claim 13.

Citation Information

Patent Citations

  • Negative electrode current collector as well as preparation method and application thereof

    CN112103512A

  • Negative pole piece of zinc secondary battery as well as preparation method and application thereof

    CN112635698A

  • High-performance negative-electrode-free aqueous zinc metal battery based on composite layered negative electrode current collector

    CN115764005A

  • Coating material for improving ion transfer-diffusion effect on battery interface as well as preparation method and application of coating material

    CN116606574A

  • Carbon fiber loaded copper sulfide / copper telluride nano composite material, preparation method thereof and application of nano composite material in zinc ion battery

    CN116995217A